If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = -110 + -10x Reorder the terms: 10 + 2x = -110 + -10x Solving 10 + 2x = -110 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 10 + 2x + 10x = -110 + -10x + 10x Combine like terms: 2x + 10x = 12x 10 + 12x = -110 + -10x + 10x Combine like terms: -10x + 10x = 0 10 + 12x = -110 + 0 10 + 12x = -110 Add '-10' to each side of the equation. 10 + -10 + 12x = -110 + -10 Combine like terms: 10 + -10 = 0 0 + 12x = -110 + -10 12x = -110 + -10 Combine like terms: -110 + -10 = -120 12x = -120 Divide each side by '12'. x = -10 Simplifying x = -10
| 124-3x=4x+19 | | 3x-2=13x-42 | | 54=2x | | 5x+37=13x-51 | | 2x+59=8x+11 | | 16-6n=22 | | -9-3-20x=-52 | | 7n+12n=n-6 | | 5x+35=12x-21 | | 9x-10=6x+2 | | 5(v+2)+3(v-5)=19 | | (2m+9)=15m-9 | | 8n-(5n+13)=7 | | 3m+2=5(m-1) | | 3y+12=28 | | 3-(3m-7)=43 | | 15d-12=68 | | 6y^3-y^2-2y=0 | | 14x^2+11x+3=2x^2-3x+3 | | -3y+17=3y-10 | | 6x+3=24x+18 | | 3p+2e=5.75 | | 48n^3=147n | | .36m^2=121 | | 12x-1=3+5x | | 5+2x=10x+4 | | 10p-2=4p+7 | | 4+5f=7+3f | | 4x+48= | | 6u=-15 | | 3b^3-27b=0 | | 4+5x=7+3f |